Paradigma Just Culture dan Psikologi Kriminal untuk Mencegah Deviasi Kerja dan Kejahatan Korporasi - Abu Rizal Fatwa Ramli (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2025)
Radical transformations in the modern work ecosystem have blurred the boundaries between organizational disciplinary violations and criminal acts, prompting the need for an interdisciplinary approach between Industrial and Organizational Psychology (IOP) and Criminology. This study is a systematic literature review analyzing scientific publications from 2021 to 2026 to examine the causes, forms, and mitigation strategies of workplace deviance and corporate crime. By synthesizing theoretical frameworks such as General Strain Theory, Broken Windows Theory, and the Big Five Personality Model, this study explains how individual psychological vulnerabilities interact with toxic work environments to create organizational anomie. Key findings indicate that Agreeableness serves as the strongest protective factor against deviance, while abusive supervision acts as the primary driver for criminal rationalization. Furthermore, this study explores the application of IOP within law enforcement subcultures, highlighting the importance of Just Culture Event Reviews (JCERs) in restoring legal optimism, and evaluates the ethical guidelines for artificial intelligence (AI) in occupational health psychology practice. The conclusion emphasizes that preventing workplace crime requires a paradigm shift from punitive risk management toward psychological empowerment, procedural justice, and the restoration of organizational culture.